2012
DOI: 10.1021/jp306209y
|View full text |Cite
|
Sign up to set email alerts
|

Thio-Mayan-like Compounds: Excited State Characterization of Indigo Sulfur Derivatives in Solution and Incorporated in Palygorskite and Sepiolite Clays

Abstract: Following what may mirror the recipe used by the ancient Maya civilization, consisting of a mixture of indigo and palygorskite, leading to the organic/inorganic pigment known as Maya Blue, we have switched indigo with thioindigo (TI) and a derivative (Ciba Brilliant Pink, CBP) and synthesized what was Christianized as "Maya Pink". The spectral and photophysical behavior of TI and CBP was investigated in solution and solid state (in powder and incorporated in palygorskite clays). In solution, TI was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 64 publications
0
20
1
Order By: Relevance
“…An ozonefree 450 WX enon lamp was used as the excitation source, the emission detector was either aH amamatsu R928 Photomultiplier (200-900 nm range), cooled with aP roducts for Research thermoelectric refrigerated chamber (model PC177CE005), or aHamamatsu R5509-42 (900-1400 nm range), cooled to 193 Ki naliquid nitrogen chamber (Products for Research model PC176TSCE-005), and ap hotodiode was used as the reference detector. [10,55] Fluorescence decays were measured using home-built nanosecond [56] and picosecond [57] time correlated single photon counting (TCSPC) equipments described elsewhere. [58] Different excitation sources were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An ozonefree 450 WX enon lamp was used as the excitation source, the emission detector was either aH amamatsu R928 Photomultiplier (200-900 nm range), cooled with aP roducts for Research thermoelectric refrigerated chamber (model PC177CE005), or aHamamatsu R5509-42 (900-1400 nm range), cooled to 193 Ki naliquid nitrogen chamber (Products for Research model PC176TSCE-005), and ap hotodiode was used as the reference detector. [10,55] Fluorescence decays were measured using home-built nanosecond [56] and picosecond [57] time correlated single photon counting (TCSPC) equipments described elsewhere. [58] Different excitation sources were used.…”
Section: Methodsmentioning
confidence: 99%
“…To un-derstandt he precise nature of the indigo-palygorskite interaction and its relationt ot he stability and shade of the pigment, exhaustive studies of both archaeological and synthetic MB samples have been performed. Several new indigo-based hybridm aterials have been prepared, such as indigo-sepiolite, [9][10][11] indigo-silicalite [11,12] and indigo-laponite, [13] as well as hybrids fromi ndigo derivatives such as thioindigo [10] and indigocarmine (indigo-5,5'-disulfonic acid disodium salt). [14,15] Like indigo, indigo carmine is ab lue dye extensively used in the textile industry,s pecifically in the blue jeans industry.H ybrids containing this dye have been prepared by its intercalation in layeredd ouble hydroxides (LDHs).…”
Section: Introductionmentioning
confidence: 99%
“…In solution, it can be present in three forms: the (neutral) keto, , the (reduced) leuco, and the (oxidized) dehydroindigo (DHI) species, each of them presenting very different spectral and excited-state characteristics. However, in contrast with what happens with keto indigo, with the leuco and DHI species, (photo)­isomerization can occur. , Indigo is also one of the key constituents of the first organic–inorganic hybrid, Maya Blue, in which the clay palygorskite imparts an additional stability to the dye. The correct structure (including the interaction of the molecule with the inorganic host) is still a theme of debate. In recent years, particular attention has been directed toward understanding the mechanisms behind the decay of excited indigo, and parent molecules such as indigocarmine. It was shown both experimentally and theoretically that the high stability of indigo is linked to an excited-state proton transfer (ESPT) process, ,, although previous reports, based on studies with a tetramethyl indigo derivative, suggested the absence of ESPT in indigo.…”
Section: Introductionmentioning
confidence: 99%
“…'Maya Powder' hybrid pigments were prepared by compounding palygorskite with thioindigo and Ciba Brilliant Pink, respectively. The results showed that the mixture of palygorskite and two indigo sulfur derivatives displayed remarkable stability toward organic solvents, acids, and alkalis [15]. For sepiolite/basic red 46 hybrid pigments, the sepiolite was believed to protect the basic red 46 molecules from the attack of acid, base, heat and ultraviolet light [16].…”
Section: Introductionmentioning
confidence: 99%